Influence of Solvent Polarity on Phytochemicals, Antioxidants, and Antimicrobial Properties of Delphinium denudatum: A Medicinal Herb from Sainj Valley, Himachal Pradesh, India - Kiran Kumari; Priyanka Adhikari; Anita Pandey; Sher Singh Samant; Manohar Lal; Veena Pande (Pandawa Institute, 2024)
Plants with medicinal properties play an important role in pharmaceutical industries for their disease prevention and treatment applications. Delphinium denudatum, commonly known as jadwar, is an important medicinal plant of the Himalayan region. Therefore, in the present study, the effect of solvent polarity (using seven different solvents i.e., methanol, ethanol, acetone, chloroform, ethyl acetate, hexane, and water separately) was estimated for its secondary metabolites production, antioxidants, and antimicrobial activities. Among the seven different extracting solvents used, the methanol extract of leaf rendered the highest phenolic content (80.52 mg GAE/g (dry weight (dw)). Acetone extracts for the shoot were found to be most efficient with the extraction of the highest flavonoid content (57.53 mg QE/g (dw) while the methanol extract of root rendered the highest tannin content 18.78 mg TAE/g (dw). Likewise, the methanol extract of the leaf showed the highest flavonol content 34.76 mg QE/g (dw). For antioxidant activity, the IC50 value for ABTS activity ranged from 35.15 to 103.08 µg/mL, and for DPPH activity it was 75.23 to 256.21 µg/mL. Further, all the plant parts i.e., leaf, shoot, and root, showed antimicrobial activity against Bacillus subtilis, Escherichia coli, and Serratia marcescens having MIC between 400 to 900 µg/mL. Among all the tested plant parts, polar solvent leaf extracts had higher antioxidant activity. Furthermore, phenols, flavonols, tannins, and ABTS activity from leaf, shoot, and root have shown a positive relation with solvent polarity. In all three plant parts; phenols, flavonols, and tannin positively correlate with antibacterial activity. The present study further revealed that the secondary metabolites in the leaf, shoot, and root extracts of D. denudatum are an excellent source of antioxidant and antimicrobial activities, thus validating the species’ therapeutic potential.